2015
DOI: 10.2174/1381612821666150820100812
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Colloids as Smart Vehicles in Cancer Therapy

Abstract: Cancer disease is one of the leading causes of morbidity and mortality worldwide, with approximately 14 million new cases and around 8 million cancer-related deaths yearly. Estimates expect to increase these figures over the next few years. Therefore, it is very important to develop more effective and targeted therapies. Polysaccharides are widely used for biomedical and pharmaceutical applications due to their interesting properties, and can be utilised in the production of nanovehicles for drug delivery, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…However, Gd-based CAs can produce toxic effects, not only in patients with renal impairment, as firstly described, but also in patients with normal renal function, as demonstrated by subsequent studies, in which the accumulation of Gd was observed in different tissues, including brain, kidneys, and bone [6,7]. In the last few years, there has been a growing interest in the development of new CAs based on nanotechnology in order to overcome this limitation [8][9][10][11]. In this sense, bi-magnetic core-shell nanoparticles (NPs) have emerged as a very promising option for the development of new MRI CAs with outstanding magnetic properties [12][13][14].…”
Section: Introductionmentioning
confidence: 91%
“…However, Gd-based CAs can produce toxic effects, not only in patients with renal impairment, as firstly described, but also in patients with normal renal function, as demonstrated by subsequent studies, in which the accumulation of Gd was observed in different tissues, including brain, kidneys, and bone [6,7]. In the last few years, there has been a growing interest in the development of new CAs based on nanotechnology in order to overcome this limitation [8][9][10][11]. In this sense, bi-magnetic core-shell nanoparticles (NPs) have emerged as a very promising option for the development of new MRI CAs with outstanding magnetic properties [12][13][14].…”
Section: Introductionmentioning
confidence: 91%
“…Numerous types of nanovehicles have been developed, and many polysaccharide-based nanovehicles have been used for the delivery of anti-cancer drugs, some of which may interact with membrane receptors. (See Caro and Pozo for an overview on the application of polysaccharides as nanovehicles in cancer therapy [ 95 ]). Specialised polysaccharide-based nanovehicles may be suitable for the delivery of mangiferin.…”
Section: Bioavailability and Delivery Of Mangiferinmentioning
confidence: 99%
“…After intravenous administration, IONPs have been described to accumulate in tumors due to the EPR (Enhanced Permeability and Retention) effect. This passive transport is determined by the high vascularization of tumors, and therefore increased blood flow, together with increased vascular permeability and poor lymphatic drainage [ 261 ]. Efremova et al [ 262 ] developed IONPs for diagnosis of breast cancer in a heterotopic model.…”
Section: Applications Of Ionps In Mrimentioning
confidence: 99%